2019
DOI: 10.1128/mspheredirect.00027-19
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Biomarkers Associated with Sterile Protection Induced by Controlled Human Malaria Infection under Chloroquine Prophylaxis

Abstract: Infection by Plasmodium parasites has been a major cause of mortality and morbidity in humans for thousands of years. Despite the considerable reduction of deaths, according to the WHO, over 5 billion people are still at risk, with about 216 million worldwide cases occurring in 2016. More compelling, 15 countries in sub-Saharan Africa bore 80% of the worldwide malaria burden. Complete eradication has been challenging, and the development of an affordable and effective vaccine will go a long way in achieving el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 62 publications
(111 reference statements)
0
55
0
Order By: Relevance
“…Anti-sporozoite antibody response is a strong contributor towards protective immunity 36,38,62 . In our Sporozoite Neutralization Assay, all mice were protected following the inoculation of sporozoites with sera from mice immunized with PbAGT8-OE-CVac parasites, indicative of a strong anti-sporozoite antibody response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-sporozoite antibody response is a strong contributor towards protective immunity 36,38,62 . In our Sporozoite Neutralization Assay, all mice were protected following the inoculation of sporozoites with sera from mice immunized with PbAGT8-OE-CVac parasites, indicative of a strong anti-sporozoite antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-described that anti-sporozoite humoral immunity generated by whole sporozoite vaccine is mostly directed towards CSP [36][37][38] . We next wanted to explore the targets of the anti-sporozoite antibody associated with sterile protective immunity in mice immunized with PbATG8-OE-CVac.…”
Section: Pbatg8-oe-cvac Parasites Trigger a Broad But Pbcsp-specific mentioning
confidence: 99%
“…Until fairly recently, technology has seriously limited the practicality of comprehensive screening for novel clinically important candidates, but that may be about to change. The authors of a recent report in mSphere (3) thus combined the remarkable ability of controlled human malaria infection (CHMI) to induce protective immunity (4) with the possibility of identifying important antibody reactivities mediating it, by employing large protein arrays including thousands of antigens (5). The analysis by Obiero et al (3) of an array covering more than 90% of the P.…”
Section: Finding the Needle(s) In The Haystackmentioning
confidence: 99%
“…However, chloroquine has been used as an autophagy inhibitor in experimental studies investigating host autophagy in hepatocytes during sporozoite development [ 36 ]. On the other hand, the protection against Plasmodium parasites has been shown in animal and human experimental studies when individuals are immunized with infectious sporozoites under the cover of chloroquine chemoprophylaxis [ 37 •• , 38 , 39 • ]. Although the role of chloroquine in these studies was to suppress following blood stage parasites, whether chloroquine induces autophagy inhibition or exerts an immunomodulatory effect has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, RAS immunization under prophylaxis with or without chloroquine induced equally strong CD8 + T cells responses [ 40 ], suggesting that chloroquine’s effect was on other, as yet unknown mechanism(s) or on other cells. Interestingly, a recent study showed that humans immunized with live sporozoites under chloroquine chemoprophylaxis reacted to a broad repertoire of novel antigens in both breadth and magnitude, as assessed by a comprehensive P. falciparum protein microarray of blood [ 39 • ]. Furthermore, the direct effect of chloroquine/primaquine prophylaxis/treatment doses on vaccination using model antigens in mice was investigated and it was found that chloroquine clearly modulates antigen-specific B cell responses [ 64 ].…”
Section: Introductionmentioning
confidence: 99%